Revised chronology for late Pleistocene Mono Lake sediments based on paleointensity correlation to the global reference curve - Zimmerman, Susan H.; Hemming, Sidney R.; Kent, Dennis V.; Searle, Stephanie Y. (2006)
Lakes are highly sensitive recorders of climate processes, but are extremely difficult to correlate precisely to ice-core and marine records, especially in the absence of reliable radiocarbon dates. Relative paleointensity (RPI) of Earth's magnetic field is an independent method of correlating high-resolution climate records, and can be applied to both marine and terrestrial sediments, as well as (inversely) correlated to the cosmogenic nuclide records preserved in ice cores. Here we present the correlation of an RPI record from Mono Lake, California to GLOPIS, the Global PaleoIntensity Stack, which increases the age estimation of the basal Mono Lake sediments by > 20 000 yr (20 kyr), from ∼40 ka (kyr before present) to 67 ka. The Mono Lake sediments thus preserve paleoclimatic records of most of the last glacial period, from 67 to 14 ka. In addition, the paleointensity-based age of 40 ka for the geomagnetic excursion preserved at Mono Lake indicates that this is a record of the global Laschamp excursion.